Consequences of diabetes on the quality of life of users from the perspective of health professional (Research, Society and Development, 2020)
The present study aims to verify the impact of diabetes on the quality of life of users from the perspective of health professionals. This is a qualitative research, carried out with 14 health professionals who work with people with diabetes treated in primary care. Data collection was carried out from April to October 2015 through semi-structured interviews with the guiding question. When identifying the impairment of diabetes in the quality of life of users from the perspective of health professionals, it was identified that it can interfere negatively in the physical, psychological, social and environmental scope of people affected by diabetes. It is concluded that identifying the impairment of diabetes in the quality of life of users from the perspective of health professionals will enable the planning of health promotion actions and the prevention of complications of individuals with diabetes treated in primary care.